(untitled) (American Journal of Islam and Society, 2012)
Shabnam Holliday’s Defining Iran: Politics of Resistance is a timely investigation of the Iranian national identity. Through careful discursive analysis of a number of texts, including primary sources – speeches, statements, and interviews – as well as articles on the Iranian identity in general and national identity in particular, Holliday seeks to show how discourses and counter-discourses emerge and shape the ways Iranians imagine and define their national identity. Such deconstruction regards texts produced since the Pahalvis reign as a preface to her main focus on those produced during and after Seyyed Mohammad Khatami’s presidency. By looking at the genealogy of tensions and dynamics between Irānīyat (referring to pre-Islamic Iran), Islāmīyat (referring to Islam, namely Persian Shi’i), and the Western influences in defining what it means to be Iranian, Holliday illustrates the roots of the “contemporary Iranian national identity” and “Iranian cosmopolitanism” (127) ...